Concerted cultivation in early childhood and social inequalities in cognitive skills: Evidence from a German panel study. (April 2021) - Mikus, Karoline; Tieben, Nicole; Schober, Pia S.
Highlights: High socioeconomic status (SES) parents more often enrolled their children in organized music and sports. High SES parents were more likely to engage in parent-child reading. Family SES was positively related to children's skill growth in math and reasoning. Despite SES differences, only music classes explained cognitive skill differences. Abstract: According to Lareau's (2003) concept of concerted cultivation, upper and middle-class parents aim more systematically to promote their children's skills in various ways in comparison with lower class parents. These differences in parenting are assumed to affect children's skill development. Whereas Lareau developed her concept for families with elementary school children, and much of the subsequent literature has focused on this age group or older, we argue that concerted cultivation is likely to be visible already during early childhood. Therefore, we investigated if participation in organized leisure activities and parents' promotion of cognitive stimulation during early childhood—as two indicators of concerted cultivation—explain later differences in cognitive skills. We furthermore examined if concerted cultivation mediates the association between social background and cognitive skills of children. We drew on longitudinal data from 1, 632 children in the Starting Cohort 2 of the German National Educational Panel Study (NEPS). We show that parents with high socio-economic status are more likely to enroll their 5-year-old children in organized leisure activities and to read to them daily. Results from lagged dependent variable regressions indicate that only enrollment in music mediates the relationship between parental socio-economic status and children's skill development in math and reasoning. Our study highlights the prevalence of concerted cultivation as a parenting style of the German middle-class already during early childhood. Nevertheless, it only moderately contributes to children's cognitive skill development. Our mediation analysis showed that only music participation explained a modest portion of the background-specific differences in math and reasoning skills.